2019
DOI: 10.1002/jclp.22829
|View full text |Cite
|
Sign up to set email alerts
|

Psychological trajectories of mothers and fathers following their child's diagnosis of a life‐threatening illness or injury: A longitudinal investigation

Abstract: Objective Explore the mental health trajectories of parents following their child's life‐threatening illness/injury. Methods Participants were 217 parents (mean age: 34.9–40.0; 66 fathers) of 165 children who presented to a tertiary hospital with a life‐threatening illness/injury. Parents completed questionnaires about their mental health and psychosocial stressors within 4 weeks of the child's illness/injury (T1), and 4 months (T2), 7 months (T3), and 19 months (T4) postdiagnosis. Results For both mothers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Our finding that the proportion of caregivers with psychologic distress increased at 12 months after decreasing steadily over the prior three time points is consistent with literature demonstrating that many caregivers experience delayed responses following their child’s critical illness ( 6 , 10 , 39 ). There was a small but important number of caregivers who experienced greater distress following their child’s hospitalization than at the time of admission, and this group increased to 8.6% of caregivers by 1 year after admission.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that the proportion of caregivers with psychologic distress increased at 12 months after decreasing steadily over the prior three time points is consistent with literature demonstrating that many caregivers experience delayed responses following their child’s critical illness ( 6 , 10 , 39 ). There was a small but important number of caregivers who experienced greater distress following their child’s hospitalization than at the time of admission, and this group increased to 8.6% of caregivers by 1 year after admission.…”
Section: Discussionsupporting
confidence: 91%
“…following their child's critical illness (6,10,39). There was a small but important number of caregivers who experienced greater distress following their child's hospitalization than at the time of admission, and this group increased to 8.6% of caregivers by 1 year after admission.…”
Section: Observational Studymentioning
confidence: 99%
“…While fathers may initially adapt faster to their child's life-threatening illness/injury, they may experience worse mental health in the long-term when compared to mothers. 33 Future research recruiting both parents would allow better understanding of the impact of childhood cancer on the family and parent's long-term HRQoL. Furthermore, lower educational attainment is a risk factor for poorer HRQoL, 34 and the results obtained here may not reflect the experiences of parents with lower educational attainment during their child's survivorship years.…”
Section: Limitationsmentioning
confidence: 81%
“…Additionally, Judge et al reported that maternal PTSS levels were correlated with child behaviour up to 12 months post PICU admission (76). Longitudinal data from fathers remains scarce, however reports have shown paternal rates of post-traumatic stress disorder (PTSD) to be lower than maternal PTSD at 12 months (77,78), which is argued to be the result of the predominantly maternal role of caregiving and subsequent differing perceptions of how life threatening the child's illness is (78,79). Whether it is acute or long-term, there is a clear link between child and parent psychosocial outcome, which needs awareness and recognition from PICU admission to beyond discharge (4).…”
Section: Parent/family Factorsmentioning
confidence: 99%